Metal–peptide rings form highly entangled topologically inequivalent frameworks with the same ring- and crossing-numbers - Tomohisa Sawada (Nature Portfolio, 2019)
For interlocking ring structures, knot theory predicts that the number of topologically different links increases with ring and crossing number. Here, the authors use a peptide folding-and-assembly strategy to selectively realize two highly entangled catenanes with 4 rings and 12 crossings, representing two of the 100 predicted topologies with this complexity.